STRATEGI INFLUENCER MARKETING PADA RAHSA NUSANTARA DALAM MENINGKATKAN BRAND AWARENESS - Ayesha Anzani Putri Dinanti Gunawan; Nurillah Jamil Achmawati Novel; Sri Ayu Budiyanti (POLITEKNIK LP3I JAKARTA, 2023)
The increasingly fierce business competition in this digital era requires business people to be more creative in building strategies to compete. In choosing a product, consumers will most likely choose a brand that they already know. Therefore, a company must choose the right strategy in increasing brand awareness. In this digital era, digital marketing is an important strategy in the marketing activities of a business, one of which is through the use of influencer marketing. Influencer marketing is a promotional activity through individuals who have a large following and strong influence on social media. This strategy is used by Rahsa Nusantara to increase brand awareness in the wider community. This research aims to find out how the implementation of influencer marketing at Rahsa Nusantara. The type of method used in this research is descriptive qualitative by conducting interviews and participant observation. The results of this study show that Rahsa Nusantara has successfully implemented an influencer marketing strategy through collaboration with influencers on Instagram and TikTok who have personas and target audiences that match Rahsa Nusantara to increase brand awareness. Keywords: Marketing, Influencer, Digital Marketing, Influencer Marketing, Brand Awareness